Avaliação da capacidade antioxidante in vitro de novos compostos mono e disseleneto - Stefanello, Sílvio Terra (2013)
The antioxidant action of organic selenium compounds, as well as ebselen and diphenyl diselenide (DPDS), is closely connected to its ability of generating the selenol group. (In) this study it was evaluated the in vitro antioxidant effect of new mono and diselenide compounds, where it was compared whether the formation of p-methyl-selenol from compounds 1-phenyl-3-(p-tolylselanyl)propan-2-amine (C1) and 1,2-dip-tolyldiselenide (C4) and o-methoxy-selenol from compounds 1-(2-methoxyphenylselanyl)-3-phenylpropan-2-amine (C2) and 1,2-bis(2-methoxyphenyl) diselenide (C3) may be involved with their antioxidant effects. The mono and diselenide compounds were tested in their Fe(II) and sodium nitroprusside (SNP)-induced lipid peroxidation in rat brain and liver homogenates and also in their antioxidant ability in phosphomolybdenum test-reductionand and DPPH radical. Besides, the effects of the compounds in the antioxidant enzymes thioredoxin reductase (TrxR) and glutathione peroxidase (GPx) were quantified. The new compounds oxidant effects were investigated through the thiol oxidase assay and the cellular viability of isolated leukocytes. The results demonstrated that the compounds obtained a significant reduce on the lipid peroxidation induced by different pro-oxidants, as well as an antioxidant effect similarly when compared to ascorbic acid equivalents. In the same manner, the compounds did not present thiol oxidase activity. Furthermore, they did not preset any decrease on the cellular viability of leucocytes. The compounds C1 and C2 did not show mimetic activity of GPx enzyme or had a substrate effect on TrxR enzyme, probably due the amino group presence on their chemical structures which must have inhibited the selenol formation. However, DPDS analog-compounds presented a mimetic activity of GPx, as well as they showed an increase in the TrxR activity, presumably due the formation of the selenol groups (p-methyl-selenol and o-methoxy-selenol).